2019
DOI: 10.1016/j.clinbiomech.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The stabilising effect by a novel cable cerclage configuration in long cephalomedullary nailing of subtrochanteric fractures with a posteromedial wedge

Abstract: Background: Clinical studies suggest that an adjunctive cerclage in intramedullary nailing of subtrochanteric fractures improves the outcome. Despite this, to what extent various cerclage configurations influences the fixation strength, remains undocumented. We tested the hypothesis that the stability of subtrochanteric fractures with a posteromedial wedge treated with long cephalomedullary nail varies with cerclage configuration. Methods: 40 composite femurs with a subtrochanteric osteotomy including a poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The CM nail has been featured in literature describing the clinical outcomes for long (Kuzyk et al, 2012;Kane et al, 2014;Vopat et al, 2015;Jin et al, 2018;Mukherjee et al, 2019) and short (Jones et al, 2006;El-Dessokey and Mohammed, 2013;Kwak et al, 2018) nails in general (Hou et al, 2013;Okcu et al, 2013;Boone et al, 2014;Kleweno et al, 2014;Vaughn et al, 2015;Dunn et al, 2016;Horwitz et al, 2016). Okcu et al (2013) compared between 15 short nails versus 18 long nails and indicated that the time of the operation was longer in the fixation with long nails, though they needed shorter follow up.…”
Section: Introductionmentioning
confidence: 99%
“…The CM nail has been featured in literature describing the clinical outcomes for long (Kuzyk et al, 2012;Kane et al, 2014;Vopat et al, 2015;Jin et al, 2018;Mukherjee et al, 2019) and short (Jones et al, 2006;El-Dessokey and Mohammed, 2013;Kwak et al, 2018) nails in general (Hou et al, 2013;Okcu et al, 2013;Boone et al, 2014;Kleweno et al, 2014;Vaughn et al, 2015;Dunn et al, 2016;Horwitz et al, 2016). Okcu et al (2013) compared between 15 short nails versus 18 long nails and indicated that the time of the operation was longer in the fixation with long nails, though they needed shorter follow up.…”
Section: Introductionmentioning
confidence: 99%